THE KOMPILASI HUKUM ISLAM AND DEBATES ON SHARI’A Reconsidering Islamic Law in Indonesia - Nasir, Mohamad Abdun (Al-Ahkam, 2012)
The discourses on the application of shari’a law through state enforcement have become public concerns in Indonesia and constituted a controversial issue. The idea of the application has been brought up by a number of Muslim politicians and Muslim groups and organizations that consider shari’a the best solution for the multi-dimension of socio-economic and political crisis upon the downfall of the New Order Regime in 1998. They believe that shari’a enforcement not only fits the spirit of democracy, assuming that the majority of population in the country is Muslims, but also offers a comprehensive solution to the crisis. Unfortunately, this idea is not grounded on a comprehensive apprehension to the nature of shari’a itself and pluralistic Indonesian society but more on political impetus, namely a strong plea to realize an Islamic state that integrates the state and religion and Islam and politics. By examining the Kompilasi Hukum Islam, as one example of shari’a legislation in Indonesia, this article demonstrates the problems of Islamic reform that most proponents of shari’a application have overlooked. It argues that application of religious law by the state must consider the methodology of the law and its impacts for broader society.***Wacana tentang penerapan hukum Islam (syari’ah) melalui kekuasaan negara telah menjadi perhatian publik di Indonesia dan menimbulkan isu-isu kontroversial. Ide tentang penerapan itu telah dibawa oleh sejumlah politisi, kelompok, serta organisasi yang menganggap syari’ah sebagai solusi terbaik atas krisis multi dimensi, sosial, ekonomi, dan politik pasca jatuhnya rezim Orde Baru pada tahun 1998. Mereka percaya bahwa penegakan hukum Islam tidak hanya cocok dengan semangat demokratisasi, karena asumsi bahwa mayoritas penduduk di negara ini Muslim, namun juga menawarkan solusi yang komprehensif bagi krisis tersebut. Sayangnya, hal ini tidak didasarkan pada pembacaan yang komprehensif terhadap sifat syari’ah itu sendiri dan terhadap kondisi sosial masyarakat Indonesia yang majemuk, melainkan lebih pada dorongan politik, yaitu dorongan yang kuat untuk mewujudkan sebuah negara Islam yang mengintegrasikan negara dan agama serta Islam dan politik. Dengan menganalisis Kompilasi Hukum Islam, sebagai salah satu contoh produk hukum Islam di Indonesia, muncul argumentasi bahwa penerapan hukum agama oleh negara harus mempertimbangkan metodologi hukum dan dampaknya bagi masyarakat luas.***Keywords: Kompilasi Hukum Islam, shari’a, changes, response, Islam-state relations, Indonesia